1992
DOI: 10.2307/256475
|View full text |Cite
|
Sign up to set email alerts
|

Role of Individual Attachments in the Dissolution of Interorganizational Relationships.

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Academy of Management is collaborating with JSTOR to digitize, preserve and extend access to The Academy of Management Journal.In this study, we propose that changes affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
268
1
13

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(295 citation statements)
references
References 41 publications
13
268
1
13
Order By: Relevance
“…However, to the extent that these exchange relationships are mutually beneficial to boundary personnel, they may endure for some time, resulting in repeated losses for either or both organizations. This is consistent with Seabright et al (1992) suggestion that boundary personnel with close ties resist IOR switching behaviours even when the resource fit between the two organizations no longer exists.…”
Section: Reciprocation Patterns and Exchange Outcomessupporting
confidence: 90%
See 1 more Smart Citation
“…However, to the extent that these exchange relationships are mutually beneficial to boundary personnel, they may endure for some time, resulting in repeated losses for either or both organizations. This is consistent with Seabright et al (1992) suggestion that boundary personnel with close ties resist IOR switching behaviours even when the resource fit between the two organizations no longer exists.…”
Section: Reciprocation Patterns and Exchange Outcomessupporting
confidence: 90%
“…Boundary personnel are organization members who interact formally and informally with the personnel of other organizations (Arndt 1979;Seabright et al 1992). Favours between and amongst boundary personnel can take a variety of forms as the following examples illustrate After a fire that destroyed much of a firm, business acquaintances extended credit at very favourable terms so that the owner could rebuild his business (Larson 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Skilful management of an ending process is of importance to both parties. The ending of business relationships may stress the employees of both parties, to the point where they consider leaving the company (Seabright, Levinthal, and Fichman 1992). If an employee is lost then the remaining relationship energy (see Havila and Wilkinson 2002), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the audit committee members that are interlocked with auditors have been suggested to have a higher influence on the decision making of the clients compared to other parties (e.g., board of directors) that also have the potential to have interlocking relationships with the auditor (Seabright et al, 1992;Jubb, 2000). Furthermore, Kalbers and Fogarty (1993) stressed on the audit committee legitimacy and power and the importance of both that may be represented by the committee size.…”
Section: Literature Reviewmentioning
confidence: 98%